Desenvolvimento de formas farmacêuticas sólidas e semissólidas contendo piperina associada a nanocarreadores - Weber, Julia (2018)
The possibility of associating natural actives with nanostructured systems appears as a less invasive treatment option for the organism. This is because, nanoparticles are able to control the release and attenuate the toxic effects of the associated active substance. Based on this, this study aims at the development of pharmaceutical forms for topical and rectal use from nanocarriers containing piperine. Initially, polymeric nanocapsules (PIP-NC), nanoemulsions (PIP-NE) and coated nanoemulsions (PIPC- NE) containing piperine were prepared by the interfacial deposition method of preformed polymer and spontaneous emulsification, respectively. The formulations were characterized in relation to pH, mean diameter, polydispersity index (PdI), zeta potential, bioactive content and encapsulation efficiency. They were also evaluated for bioadhesive potential, irritation potential, in vitro release profile and photodegradation. The PIP-NCs were evaluated for cytotoxic potential against HT-29 tumor cells. The dry products (PIP-NC-L) were prepared from the NC-PIPs by lyophilization and characterized in therms yield, distribution and particle size and piperine content. The powders were embedded in PEG400: PEG4000 (20:80, SR1-PIP-NC) and PEG400: PEG4000: Oily Extract (45: 50: 5, SR2-PIP-NC) suppositories and evaluated for mean weight, content uniformity, morphological analysis, release and permeation / penetration in vitro. From the NE, the nanogels (NG-PIP-NE) were prepared by the extrusion method and evaluated for pH, mean diameter, bioactive content, spreadability, rheological behavior, release and permeation / penetration in vitro. The nanostructures showed a mean diameter in the nanometric range (120-170 nm), PdI <0.25 and positive zeta potential (NC and C-NE) and negative (NE). The piperine content was close to the theoretical (1.0 mg / mL) and the encapsulation efficiency was around 100%. The PIP-NC and PIP-C-NE were slightly irritant and irritant, respectively; while PIPNE was not irritating. The PIP-NC and PIP-C-NE presented bioadhesive potential. As for the release study, the nanostructures were able to control the release of piperine. The PIP-NC and PIP-NE protected the piperine from photodegradation, unlike PIP-C-NE. In the cytotoxicity assay, the PIP-NCs were able to reduce cell viability. The PIP-NC-L presented near 100% yield, bioactive content close to theoretical (7.74 ± 0.03 mg / g), particle size distribution in nanometric and micrometric bands with a mean size of 150-160 nm. The suppositories showed white to slightly yellowish coloration, characteristic odor of the base, homogeneous appearance, no cracking or blistering; diameter from 9 to 10 mm and length from 33 to 35 mm; average weight around 3.0 g. The bioactive content was close to the theoretical (5.90 mg / suppository). The SR2 ensured better distribution / dispersion of the powders at the base. In vitro studies (dialysis bag) and permeation/penetration (inverted intestine) studies found the influence of the base on the bioactive delivery in membranes and biological fluids, as SR2 modified the release and permeation / penetration of piperine. Nanogels caused an increase in mean droplet size (230 ± 6 nm); bioactive content close to theoretical (0.57 mg / g); pH and viscosity compatible with topical application. The in vitro release study (dialysis membrane) confirmed the ability of NG-PIP-NE to deliver a greater amount of bioactive. However, in the permeation / penetration study (porcine skin) there was no difference for piperine present in the skin layers relative to the organogel with non-associated piperine.